Factors influencing behavioural intention to use MOOCs - Bilal Khalid; Marcin Lis; Wornchanok Chaiyasoonthorn; Singha Chaveesuk (Engineering Management in Production and Services, 2021)
Abstract This analysis aimed to investigate the factors influencing the behavioural intention to use Massive Open Online Courses (MOOCs) in Thailand and Pakistan. The study was geared towards exploring the MOOCs, a relatively new technology platform allowing the spread of education and learning in various areas and fields and surpassing traditional online courses. The study adopted the UTAUT model with additional two variables of perceived autonomy and absorptive capacity. A quantitative method was applied using primary data collected from a sample of 490 and 513 respondents from Thailand and Pakistan, respectively. The sample size was composed of students in institutions of higher learning who were aware of MOOCs or intended to use them in their studies. The analysis was conducted using the Confirmatory Factor Analysis (CFA) and multi-group structural equation modelling (SEM). The study found that four variables (social influence, absorptive capacity, facilitating conditions and perceived autonomy) significantly influence the student intention to use MOOCs in Thailand and Pakistan. However, two variables (performance expectancy and effort expectancy) did not influence the student intention to use MOOCs in Thailand and Pakistan. The results indicated that the findings between the two countries were invariant. This study extended the model by Venkatesh et al. (2003), including two additional variables, the perceived autonomy and absorptive capacity. The study indicated various aspects related to the response of students using MOOCs. This study is especially beneficial during the COVID-19 pandemic for determining factors that officials of higher institutions of learning should consider when implementing MOOCs and associated online learning programs to deliver quality education to students.
Keywords: Online Learning and Analytics; Technology Adoption and User Behaviour; E-Learning and COVID-19